Pengaruh Media Sosial Dalam Kasus Kekerasan Seks Pada Anak Dibawah Umur - Anisah, Aura; Lewoleba, Kayus K (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The family unit is incomplete without children, they can be a source of happiness for parents and the nation's next generation. The phenomenon of development in the digital era, especially in the field of communication, apart from having a positive impact on life, can also have a negative impact. The use of social media X, Tiktok, Youtube, Instagram or Facebook by irresponsible people endangers children's safety. Tragically, social media has contributed to a rise in incidents of sexual assault against minors To ensure children's safety from the dangers of sexual violence in the digital era, the government has created a Child Protection Law which involves parents, the local community and the government to safeguard children. The purpose of this work of literature is to investigate and clarify the ways in which sexual assault is harmful and to provide strategies for preventing it from an early age. Methods used in this investigation are based on literature that is sourced from libraries, appropriate to the problem being studied as a data source.